Implementing Frontloading Strategy in an Attempt to Trigger the Improvement of Students' Vocabulary Mastery - Hoban, Elisabeth Regina; Balik, Lusiana Mariyeta; Janggo, Wendelinus Oscar (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2024)
In this study, the authors used the frontloading strategy to improve students' vocabulary. The main objectives of this study were to describe the implementation of the frontloading strategy in vocabulary instruction and to determine the extent to which students' vocabulary skills improved after instruction through the use of the front-loading strategy. This study is a classroom action research conducted in two cycles. Data was collected through observation, testing and interviews. Data from observations, tests and interviews from each cycle were analyzed quantitatively and qualitatively. The implementation of the frontloading strategy for vocabulary teaching in Class XI 3 of St. John Paul II Catholic Senior High School was carried out in two cycles. The participants in this study were 30 students. The result of this study shows that using frontloading strategy can improve students' vocabulary skills. This is evidenced by the students' test scores, which increased in each cycle, namely Cycle 1 and Cycle 2. In the first cycle, the student's average score was 50%, in the second cycle the average score was 83.33%. It can be concluded that the frontloading strategy can improve students' ability to master vocabulary and also improve teaching.